DOI: 10.31979/etd.3yez-nsaz
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Persistence of Students with Autism Spectrum Disorder in Higher Education Settings

Abstract: Students with autism spectrum disorder (ASD) who transition to higher education environments vary in their level of skills when engaging in social activities. Current research is limited about supporting college students with ASD socially in the classroom. The purpose of this qualitative study was to investigate the perceptions of faculty regarding the social skills support needs of students with ASD in classroom settings that can influence the level of achievement of academic goals in postsecondary environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Currently, several studies on the utterance of children with autism revealed that the language development of autistic children is much slower than that of normal children of the same age. Regarding the receptive ability as well as the expressive utterance of autistic children, there is a remarkable delay compared to normal children of the same age (Eaves, Ho, 2004;Luyster, Lopez, Lord, 2007;Jessica Rodriguez, 2019). The ability to receive and express autistic children is diverse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, several studies on the utterance of children with autism revealed that the language development of autistic children is much slower than that of normal children of the same age. Regarding the receptive ability as well as the expressive utterance of autistic children, there is a remarkable delay compared to normal children of the same age (Eaves, Ho, 2004;Luyster, Lopez, Lord, 2007;Jessica Rodriguez, 2019). The ability to receive and express autistic children is diverse.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the phonological characteristics of autistic children's utterances, autistic children develop their utterances slower than normal children, and autistic children have monotonous, high-pitched utterances accompanied by echolalia (Charman et al, 1997;Scott, 2012;Jessica Rodriguez, 2019). Autistic children often have unclear pronunciation, high timbre, and even intonation (Hanh, 2007).…”
Section: Introductionmentioning
confidence: 99%